Complete chloroplast genome of Sedum sarmentosum and chloroplast genome evolution in Saxifragales. - Wenpan Dong (PLoS ONE, 2013)
Comparative chloroplast genome analyses are mostly carried out at lower taxonomic levels, such as the family and genus levels. At higher taxonomic levels, chloroplast genomes are generally used to reconstruct phylogenies. However, little attention has been paid to chloroplast genome evolution within orders. Here, we present the chloroplast genome of Sedum sarmentosum and take advantage of several available (or elucidated) chloroplast genomes to examine the evolution of chloroplast genomes in Saxifragales. The chloroplast genome of S. sarmentosum is 150,448 bp long and includes 82,212 bp of a large single-copy (LSC) region, 16.670 bp of a small single-copy (SSC) region, and a pair of 25,783 bp sequences of inverted repeats (IRs).The genome contains 131 unique genes, 18 of which are duplicated within the IRs. Based on a comparative analysis of chloroplast genomes from four representative Saxifragales families, we observed two gene losses and two pseudogenes in Paeonia obovata, and the loss of an intron was detected in the rps16 gene of Penthorum chinense. Comparisons among the 72 common protein-coding genes confirmed that the chloroplast genomes of S. sarmentosum and Paeonia obovata exhibit accelerated sequence evolution. Furthermore, a strong correlation was observed between the rates of genome evolution and genome size. The detected genome size variations are predominantly caused by the length of intergenic spacers, rather than losses of genes and introns, gene pseudogenization or IR expansion or contraction. The genome sizes of these species are negatively correlated with nucleotide substitution rates. Species with shorter duration of the life cycle tend to exhibit shorter chloroplast genomes than those with longer life cycles.